PENGARUH PENGGUNAAN MEDIA AUDIO VISUAL TERHADAP TINGKAT PEMAHAMAN SISWA DALAM PEMBELAJARAN FIQH - Rusnawati (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2022)
Audio visual media is one of the learning media that can be used by teachers in learning fiqh. Audio-visual media can be a tool or intermediary when the teacher explains fiqh materials. In addition to making it easier for teachers to explain, students can understand the material more quickly and easily. Based on this, the research objectives in this paper are to determine the meaning and purpose of using audio-visual media, to find out the various audio-visual media in fiqh learning, to determine strategies for using audio-visual media in fiqh learning and to determine the effect of using media audio-visual to improve understanding of fiqh learning. In this research, the writer uses library research method or literature review. From the results of the literature review, it was found that audio-visual media is a medium that is used as an intermediary to reach the concept of ideas and experiences so that they can be captured by the senses of sight and hearing. The purpose of using audio-visual media in learning fiqh is as a teaching aid that will affect the conditions and learning environment arranged by the teacher. To be able to generate learning motivation and improve understanding of fiqh learning and the effectiveness of the learning process in delivering lesson content. Various kinds of audio-visual media that can be used in learning fiqh include motion audio-visual media and silent audio-visual media. Motion audio-visual media includes sight, hearing, and movement, and displays elements of moving images such as sound films, television, video and motion pictures. The silent audio-visual media are in the form of sound films or live pictures and television which displays sound and still images such as sound, sound sequence films, sound prints. The strategy of using audio-visual media in learning fiqh can be done by the teacher in the classroom or outside the classroom. The two places can be varied according to the conditions and conditions at the time of the learning. Because the teacher's strategy in using audio-visual media will have a very good influence on increasing student interest, motivation and learning outcomes in fiqh learning.